Work-family and family-work conflicts amongst nurses working with HIV/AIDS patients within the Limpopo Province (Capricorn and Mopani Districts) - Makola, Lehlogonolo (University of Limpopo (Turfloop Campus), 2014)
South African nursing environments are defined by extensive workloads, heightened stress levels, long working hours, reduced productivity and lack of support from supervisors. Nurses working with HIV/AIDS patients are further challenged with being exposed to death and dying patients, the stigma attached to the disease and fear of infection. These workplace characteristics lead to experiences of imbalanced work and family responsibilities which lead to W-F and F-W conflicts. The aim of this study was to explore W-F and F-W conflicts and their psychological impact on nurses working with HIV/AIDS patients at government hospitals within Capricorn and Mopani districts, Limpopo province. A convenience sample of nurses (N = 91) working with HIV/AIDS patients was used, within a cross-sectional design, to investigate the hypotheses of the study. Findings of the study did not generally support the hypotheses. However, F-W conflict predicted work satisfaction while W-F conflict predicted intention to leave job. Moreover, significant other support had a direct effect on family satisfaction while supervisor support moderated reports of W-F conflict and experiences of job satisfaction. Keywords: work-family conflict, family-work conflict, social support from supervisor, significant other support, family satisfaction, job satisfaction, family-work conflict family-work conflict
Thesis (M.A. (Psychology)) --Universtity of Limpopo, 2013
Keywords: Work-family conflict; Job satisfaction; Family-work conflict; Work environment -- Psychological aspects